Iron Metabolism Disorders for Cognitive Dysfunction After Mild Traumatic Brain Injury - Huang, Suna; Li, Su; Feng, Hua; Chen, Yujie (Frontiers in Neuroscience, 2021)
Traumatic brain injury (TBI) is one of the most harmful form of acute brain injury, and predicted to be one of the three major neurological diseases that cause neurological disabilities by 2030. A series of secondary injury cascades often cause cognitive dysfunction of TBI patients leading to poor prognosis. But there are still no effective intervention measures, which drive us to explore new therapeutic targets. In this process, the most part of mild traumatic brain injury (mTBI) are ignored, because of its initial symptoms seemed not serious. Unfortunately, the ignored mTBI accounts for 80% of total TBI, and a large part of the patients have long-term cognitive dysfunction. Iron deposition has been observed in mTBI patients and accompany with the whole pathological process. Iron accumulation may affecte long-term cognitive dysfunction from three pathways: local injury, iron deposition induces tau phosphorylation, the formation of neurofibrillary tangles; neural cells death; neural network damage, iron deposition leads to axonal injury by utilizing the iron sensibility of oligodendrocytes. Thus, iron overload and metabolism dysfunction was thought to be play a pivotal role in mTBI pathophysiology. Cerebrospinal-fluid contacting neurons (CSF-cNs) located in ependyma have bidirectional communication function between cerebral-spinal fluid and brain parenchyma, and may participate in the pathway of iron-induced cognitive dysfunction through project nerve fibers and transmitted factor, such as 5-hydroxytryptamine, etc. The present review provides overview of the metabolism and function of iron in mTBI, and to seek a potential new treatment target for mTBI with a novel perspective through combined iron and CSF-cNs.